Palermo in the 14th Century: Between Latins and Catalans - Pizzoli, Enrico (Actual Problems of Theory and History of Art, 2019)
During the Middle Ages Sicily is characterized by a great plurality of influences due to the position of the island, between the West and the East, in the Mediterranean basin making it a border land where different cultures coexisted influencing each other. The Norman dominion created a unique kind of cultural syncretism that was typical of this region until the 15th century. After the Sicilian Vespers (1282), when the island revolted against the Angevin dominion, the crown of the Sicilian kingdom was offered to Peter III of Aragon (1273/74–1337). The new king had no real power, and the baronial families, divided in Latin and Catalan fractions, ruled the island. These families showed their power through the construction of their residences, new ecclesiastical buildings and family chapels.In Palermo in the decoration of private palaces the use of Arabic stone inlay, or tarsia, becomes an expression of the Latin fraction. The stone tarsia was also used in religious buildings, such as the façade of S. Agostino church, built at the end of the 13th century, or the Calvello chapel in S. Francesco built at the beginning of the 14th century, both build by private commission. This kind of decoration during this period was probably used as a political message of the Latin families adversary to the Catalan, Iberian families that arrived to the island with the Aragon king.Only in the second half of the 14th century new architectural language appeared in buildings such as St. Antonio at Steri constructed by Manfredi III Chiaromonte († 1391), where the stone decoration was abandoned and new elements were used, such as the ribbed vaults and a rib-vaulted apse. Another Chiaramonte commission, St. Maria in Baida, shows the use of Catalan gothic motives in the architectural decoration.The focus of this paper is to underline how the island in its condition of border land was subjected to the influence of other cultures which expanded its horizons in the arts and architecture.
Keywords: Palermo; Sicily; architecture; stone tarsia; private architecture; Chiaramonte; Gothic